A Review on Microspheres: Preparation, Characterization and Applications - Galande, Prasad; Yadav, Vishal; Borkar, Smita (Asian Journal of Pharmaceutical Research and Development, 2022)
Small sphere-shaped particles are known as microspheres and their particle size range is 1micrometer to 1000 micrometer. They are free-moving, spherical particles that can be manufactured from proteins or artificial polymers. There are several methods for delivering a medicinal chemical to the target region with a regulated, prolonged release. which naturally decomposes.Microcapsules and micromatricesare two of the different types of microspheres. There are numerous varieties of microspheres that are described. Microspheres are one of the most popular varieties and provide a number of benefits.Theseprepared microspheres can be compressed or filled with a firm gelatin. There are several methods for creating microspheres, including single-emulsion, double-emulsion, solvent evaporation, phase separation coacervation, and spray drying. Microspheres are assessed using a variety of assessment methods, and they are examined in relation to a number of applications, including the delivery of vaccines, chemotherapy, ophthalmic drugs, gene therapies, and oral, nasal, and buccal drug delivery of pharmaceuticals.